Antimicrobial activity of different nanocellulose films embedded with thyme, cinnamon, and oregano essential oils for active packaging application on raspberries - Casalini, Sara; Baschetti, Marco G.; Cappelletti, Martina; Guerreiro, Adriana C.; Gago, Custódia M.; Nici, Silvia; Antunes, Maria D. (Frontiers in Sustainable Food Systems, 2023)
The study focuses on the antimicrobial activity of nanocellulose films (NFC) embedded with thyme, cinnamon and oregano essential oils for active packaging application. Firstly, the activity against model pathogenic bacteria was tested to obtain the minimum inhibitory concentration (MIC) of each oil. The tests showed that the surface area of the films and the quantity of essential oil have a strong influence on the antimicrobial effect. Then, the different active packaging systems were tested directly on packed raspberries, to study their actual commercial packaging conditions. Through 12 days storage at 1 ºC, it was observed that thyme and oregano essential oils were more effective in maintaining firmness and reducing weight loss of the fruits compared to cinnamon essential oil or controls; no significant effect was observed instead, on the other quality parameters considered. The essential oils proved to be effective in preventing fungal growth, with the synergistic effect of thyme+oregano (NAP_TO) showing the best performance.